Appropriating the Lonergan Idea. - Crowe, S. J., Frederick E. (University of Toronto Press, 2006)
A wide variety of topics is explored in this collection, from Lonergan's early academic career and the evolution of his notion of God, to the dynamic of ecclesial learning and the missions of the Trinity.